The integration process in Central Asia as a factor in ensuring the security of the region - A. A. Kerimov; G. M. Bobojonov (Современная наука и инновации)
This article examines the process of integration in Central Asia, as well as the relationship of the countries of this region with world powers. Since gaining independence, Central Asia has faced many interstate problems that have actualized issues of regional integration. The article analyzes the stages of integration, as well as the factors contributing to disintegration processes. The sides also discuss aspects of cooperation between the countries of the region in the field of water diplomacy and cross-border relations in order to strengthen borders with Afghanistan.